Urgensi English Classroom Management dalam Proses Belajar Mengajar (PBM) - Mutiara Sofa (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2019)
This paper explains about English classroom management in the teaching and learning process (PBM) in schools. Management is very important because besides being scientific, management is also the art and expertise of the teacher or educator in managing and solving various problems that arise that must be faced by the teacher in the classroom. In managing English classes a teacher is required to be able to produce intact learners in accordance with the educational function in the National Education System Act. The teacher must also be able to implement management functions in various activities in the classroom. An English teacher must be able to manage classes and master techniques in learning English. Learning techniques that can be used in English such as listen and repeat, listen and do, question and answer, substitution, draw and color, listen and identify, see differences, in a pair, group discussion, Cooperative Learning Learning, questioning and inquiry, modeling and demonstration, concept mapping, brainstorming, and also outdoor activity. English classroom management is very important for English teachers in carrying out teaching and learning in schools, so that the objectives to be achieved in learning can be carried out well so that the ability of students in mastering English is increasingly developing well in speaking, reading, listening and writing.